Developing Supplementary Material For Students’ Visual Learning Style At Vocational High School Sungai Pinang - Aulia Azmina Fajriati (Language-Edu, 2020)
Abstract This research has a purpose that aims to develop a product in the field of education. The researcher conducted some steps to evolve an appropriate supplementary book. This research is Research and Development (R&D) that is developing a supplementary book. For information, researchers use two instruments specifically, a questionnaire for students and an interview with an English teacher. For gained the data researcher used questionnaires for need analysis. Researcher conduct the research on students of Vocational High School Sungai Pinang conveyed that they need the material according to their learning style that is a visual learning style. To manage this problem, the researcher developed supplementary books based on their need. The result of tryouts the result showed that the supplementary book is suitable for the visual learner style. From the findings of the researchers, the data in which can indicate that the material in the materials is in accordance with what students need. The product achieves students’ needs in overall. Based on the results of the tryouts that can be tested by researchers, the material developed can make students more interested in learning English, and have motivation in English. Keywords: Visual learning style, Augmented Reality, Supplementary book